Avifaunal Diversity along River Tawi in Jammu Region of J&K, India - Akhter, Shahima; Sharma, Pooja (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
An avifaunal study was carried out from June 2023 to May 2024, in the River Tawi, Jammu. The study explores the variety of bird species found in this region. A total of 75 different bird species were recorded reflecting a fair degree of avian diversity. As birds play an important role in maintaining health of the ecosystem, it is necessary to continuously monitor the diversity of avifauna in order to assess the ecological status of birds and their habitats. This paper aims to provide insights into the ecological importance of the River Tawi for birdlife and highlight conservation needs.